Evaluasi Program Pengembangan SDM - Anisa fitriani; Azwa Nailafath; machdum Bachtiar (STKIP Subang, 2026)
Human Resource Development (HRD) program evaluation is an essential process in determining the effectiveness and efficiency of training and development activities within an organization. This study discusses the importance of evaluating HRD programs to measure their contribution to improving employee competence, performance, and professionalism. The evaluation process involves several aspects, including participant reactions, learning outcomes, behavioral changes, stakeholder satisfaction, and organizational impact. Various evaluation models such as CIPP, Kirkpatrick, Abruzzese, and Alspach are highlighted as frameworks for assessing training effectiveness comprehensively. In the digital era, HRD programs also play a strategic role in helping employees and educators adapt to technological advancements, including the integration of digital learning systems and artificial intelligence in the workplace. The study emphasizes that effective training programs must be based on organizational needs, supported by appropriate methods and materials, and followed by continuous evaluation. Furthermore, efficient management of costs and resources is necessary to maximize program outcomes without unnecessary expenditure. The findings indicate that systematic evaluation enables organizations to identify strengths and weaknesses in HRD programs and supports strategic decision-making for sustainable human resource improvement and long-term organizational competitiveness.